Langerhans Cell Histiocytosis Mimicking Aggressive Periodontitis. A Multidisciplinary Approach During an 8‐Year Follow‐Up Period. Issue 2 (1st May 2017) - Sakellari, Dimitra; Klonizakis, Philippos; Vlachaki, Efthymia; Dimitrakopoulos, Ioannis
Abstract : Introduction: Aggressive periodontitis (AgP), according to the diagnostic criteria set by the American Academy of Periodontology, is an infrequent periodontal disease. However, certain cases originally diagnosed as AgP due to young age and the involvement of first molars, when not responding to therapy, can diagnostically involve more severe systemic conditions such as the rare disorder Langerhans cell histiocytosis (LCH). Case Presentation: A 25‐year‐old white male, with no known systemic diseases, was referred to the Postgraduate Clinic of the Department of Periodontology and Implant Biology, Dental School, Aristotle University of Thessaloniki, Thessaloniki, Greece. Clinical and radiographic examination and comparison with a previous evaluation revealed a rapidly progressive lesion involving the molar region in all quadrants, although the patient had been treated by a periodontist during the last 2 years. Molars were extracted and biopsies taken, which demonstrated morphologic and immunohistochemical characteristics leading to the diagnosis of LCH. The patient was referred to a hematology clinic, where he received a comprehensive examination and chemotherapy. The patient did not further comply with his proposed medical treatment and therefore 2 years later appeared with a progressing lesion in the molar area. He was re‐treated by further extractions and closure of a sinus perforation. He was persuaded to continue the treatment plan and received supportive periodontal treatment every 3 months. Regular medical and periodontal checkups show that his condition remains stable during the last 5 years. Conclusion: Periodontists should be aware of rare systemic conditions mimicking AgP and immediately refer the patient accordingly.